Analysis of lower limb injury mechanism of an average Chinese pedestrian lower limb FE model in lateral impact. (24th November 2020) - Chen, Jiqing; Cheng, Renjie; Lan, Fengchong; Zhou, Yunjao
According to the statistics, lower limb injuries are the second most frequent region of traffic injuries. For the in-depth study of the biomechanical response and injury mechanism of pedestrian lower limb, the pedestrian lower limb biomechanical Finite Element (FE) model with high biological fidelity was developed and verified. By applying the proposed model, simulation studies were conducted to investigate pedestrian lower limb dynamic responses and injuries under different bumper foam filling structures and bumper collision heights during lateral impact. Simulation results demonstrated that filling the cushion foam between the bumper cover and the anti-collision beam can effectively reduce the injury index of pedestrian's lower limbs, and the trapezoidal foam structure gives better protection effect. In addition, appropriately lowering the bumper collision height can improve the car's friendliness to pedestrian's lower limbs.